(untitled) (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: Neuromuscular disorders are disorders of the neuro system that impact the muscular system. Among them are Guillain-Barré Syndrome and Myasthenic Crisis. Guillain-Barré syndrome is an autoimmune disorder of the nervous system that is polyradiculoneuropathic, characterized by weakness that radiates from the legs to the arms, torso, and face. Myasthenic crisis is a state of acute respiratory failure due to the exacerbation of Myasthenia Gravis. These two diseases are the most common types of neurodiseases found in hospital ICU patients. Objective: Determining the mortality rate of Guillain-Barré Syndrome and Myasthenic Crisis at Haji Adam Malik Central General Hospital Medan January 2021-December 2022. Methods : This study was a descriptive study with data obtained from medical records. The subjects were inpatients and outpatients with Guillain Barré Syndrome and Myasthenia Crisis, with as many as 129 patients. The subjects were selected by purposive sampling and met the inclusion and exclusion criteria. Results: A total of 40 Guillain-Barré Syndrome patients were studied, and 6 of them died. The majority were patients aged 36-50 years, and the male and female sexes were equally significant. A total of 89 patients with Myasthenic Crisis were studied, and 1 of them died, namely patients with the age category of 36-50 years and female. Conclusion: Guillain-Barré Syndrome mortality was 15%, and Myasthenic Crisis was 1.12% at Haji Adam Malik Center General Hospital Medan January 2021-December 2022. Keyword : Guillain-Barré Syndrome, Mortality, Myasthenic Crisis